Performance of Rotary Cutter Type Breaking Machine for Breakingand Deshelling Cocoa Roasted Beans - Sukrisno Widyotomo; Sri Mulato; Edi Suharyanto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2005)
Conversion of cocoa beans to chocolate product is, therefore, one of the promising alternatives to increase the value added of dried cocoa beans. On the other hand, the development of chocolate industry requires an appropriate technology that is not available yet for small or medium scale of business. Breaking and deshelling cocoa roasted beans is one important steps in cocoa processing to ascertain good chocolate quality. The aim of this research is to study performance of rotary cutter type breaking machine for breaking and deshelling cocoa roasted beans. Indonesian Coffee and Cocoa Research Institute has designed and tested a rotary cutter type breaking machine for breaking and deshelling cocoa roasted beans. Breaker unit has rotated by ½ HP power, single phase, 110/220 V and 1440 rpm. Transmission system that use for rotating breaker unit is pulley and single V belt. Centrifugal blower as separator unit between cotyledon and shell has specification 0.5 m 3 /min air flow, 780 Pa, 370 W, and 220 V. Field tests showed that the optimum capacity of the machine was 268 kg/h with 500 rpm speed of rotary cutter, 2,8 m/s separator air flow, and power require was 833 W. Percentage product in outlet 1 and 2 were 94.5% and 5.5%. Particle distribution from outlet 1 was 92% as cotyledon, 8% as shell in cotyledon and on outlet 2 was 97% as shell, 3% as cotyledon in shell. Key words:cocoa, breaking, rotary cutter, quality.